1984
DOI: 10.1128/aem.47.1.61-67.1984
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of a Mycobacterium sp. to cellulose diacetate membranes used in reverse osmosis

Abstract: The kinetics of adhesion of a Mycobacterium sp. to cellulose diacetate reverse-osmosis membranes is described. This Mycobacterium sp. (strain BT2-4) was previously implicated in the initial stages of reverseosmosis membrane biofouling at a wastewater reclamation facility. Adhesion of BT2-4 cells to the cellulose diacetate membrane surfaces occurred within 1 to 2 h at 30°C and exhibited saturation-type kinetics which conformed closely to the Langmuir adsorption isotherm (Pearson r correlation coefficient = 0.97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…In addition, a Mycobacterium sp. was shown to cause biofouling by adhering to membranes used in reverse osmosis at a wastewater reclamation facility [15]. The MBEC1 assay system, using M. phlei provided a model system in which multiple and equivalent bio¢lms could be produced and tested for susceptibility against various biocides.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Mycobacterium sp. was shown to cause biofouling by adhering to membranes used in reverse osmosis at a wastewater reclamation facility [15]. The MBEC1 assay system, using M. phlei provided a model system in which multiple and equivalent bio¢lms could be produced and tested for susceptibility against various biocides.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium strain BT12-100, an acid-fast rod-shaped organism, was used in this study. Strain BT12-100 was previously isolated from biofouled RO membranes at Water Factory 21, an advanced water reclamation facility in southern California (Ridgway et al, 1984b(Ridgway et al, , 1985. Hydrocarbon partitioning studies with this bacterium indicated a hydrophobic exterior due to cell wall mycolic acids (Bendinger et al, 1993) and binding of cells to hydroxyapatite was consistent with a net negative surface charge at pH 7.0 (unpublished).…”
Section: Bacterial Strainmentioning
confidence: 98%
“…Hydrophobic and electrokinetic forces have been similarly implicated in the adherence of bacteria to polymer membrane materials used in RO systems, such as cellulose acetate (CA) and aromatic polyamide (PA) (Flemming and Schaule, 1988;Flemming et al, 1993Flemming et al, , 1994Leslie et al, 1993;Ridgway, 1988;Ridgway and Flemming, 1996;Ridgway et al, 1985;Ridgway and Safarik, 1991). Ridgway et al (1985) demonstrated that a hydrophobic Mycobacterium strain, previously isolated from biofouled RO membranes used in wastewater reclamation (Ridgway et al, 1984a(Ridgway et al, , 1984b, attached more strongly to CA membranes than did a hydrophilic strain of Escherichia coli. Similarly, a wildtype strain of Acinetobacter phosphadevorus that elaborated hydrophobic fimbria exhibited strong affinity for CA membranes, whereas a hydrophilic isogenic mutant lacking fimbria exhibited poor attachment (Ridgway et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the hydrophobic cell cannot interact with hydrophilic surfaces, resulting in a reduction of friction and sliding on the surface. Ridgway et al [190] suggested that cell surface polypeptides, a-1,4or a-1,6-linked glucan polymers, and carboxyl ester bond-containing substances (possibly glycopeptidolipids) may be involved in mycobacterial adhesion in their study of the adhesion of a Mycobacterium sp. to a cellulose diacetate membrane used in reverse osmosis.…”
Section: Biofilmsmentioning
confidence: 99%